Lemon Peel Water Extract: A Novel Material for Retinal Health, Protecting Retinal Pigment Epithelial Cells against Dynamin-Related Protein 1-Mediated Mitochondrial Fission by Blocking ROS-Stimulated Mitogen-Activated Protein Kinase/Extracellular Signal-Regulated Kinase Pathway - Tsou, Shang-Chun; Chuang, Chen-Ju; Wang, Inga; Chen, Tzu-Chun; Yeh, Jui-Hsuan; Hsu, Chin-Lin; Hung, Yu-Chien; Lee, Ming-Chung; Chang, Yuan-Yen; Lin, Hui-Wen (Antioxidants, 2024)
Previous studies showed that NaIO3 can induce oxidative stress-mediated retinal pigment epithelium (RPE) damage to simulate age-related macular degeneration (AMD). Lemon peel is rich in antioxidants and components that can penetrate the blood–retinal barrier, but their role in retinal oxidative damage remains unexplored. Here, we explore the protection of lemon peel ultrasonic-assisted water extract (LUWE), containing large amounts of flavonoids and polyphenols, against NaIO3-induced retinal degeneration. We initially demonstrated that LUWE, orally administered, prevented retinal distortion and thinning on the inner and outer nuclei layers, downregulating cleaved caspase-3 protein expression in RPE cells in NaIO3-induced mice. The effect of LUWE was achieved through the suppression of apoptosis and the associated proteins, such as cleaved PARP and cleaved caspase-3, as suggested by NaIO3-induced ARPE-19 cell models. This is because LUWE reduced reactive oxygen species-mediated mitochondrial fission via regulating p-Drp-1 and Fis1 expression. We further confirmed that LUWE suppresses the expression of p-MEK-1/2 and p-ERK-1/2 in NaIO3-induced ARPE-19 cells, thereby providing the protection described above, which was confirmed using PD98059 and U0126. These results indicated that LUWE prevents mitochondrial oxidative stress-mediated RPE damage via the MEK/ERK pathway. Elucidation of the molecular mechanism may provide a new protective strategy against retinal degeneration.